Information needs of parents of children with congenital anomalies across Europe: a EUROlinkCAT survey - Elena Marcus; Anna Latos-Bielenska; Anna Jamry-Dziurla; Ingeborg Barišić; Clara Cavero-Carbonell; Elly Den Hond; Ester Garne; Lucas Genard; Ana João Santos; LRenée Lutke; Carlos Matias Dias; Christina Neergaard Pedersen; et al. (BMC, 2022)
Abstract Background Parents of children who have a congenital anomaly can experience significant worry about their child's health. Access to clear, helpful, and trustworthy information can provide a valuable source of support. In this study the aim was to explore the information needs of parents/carers of children with congenital anomalies across Europe. Method A cross-sectional online survey was developed in nine languages to measure parents' information needs, including: (1) the 'helpfulness'/'trustworthiness' of information received from eight relevant sources, and (2) overall satisfaction with information received. Parents/carers of children (0-10 years) with cleft lip, spina bifida, congenital heart defect [CHD] requiring surgery, and/or Down syndrome were recruited online via relevant organisations in 10 European countries from March-July 2021. Quantitative analyses using multivariable logistic regressions were performed. Results One thousand seventy parents/carers of children with a cleft lip (n = 247), spina bifida (n = 118), CHD (n = 366), Down syndrome (n = 281), and Down syndrome with CHD (n = 58) were recruited in Poland (n = 476), the UK (n = 120), Germany (n = 97), the Netherlands/Belgium (n = 74), Croatia (n = 68), Italy (n = 59), other European countries (n = 92), and not specified/non-European countries (n = 84). Most participants were mothers (92%) and aged 31-40 years (71%). Participants were most likely to rate support groups (63%), patient organisations (60%), specialist doctors/nurses (58%), and social media (57%) as 'very helpful' information sources. 'Very trustworthy' ratings remained high for specialist doctors/nurses (61%), however, they declined for support groups (47%), patient organisations (48%), and social media (35%). Germany had the highest proportion of participants who were 'very satisfied' (44%, 95% CI = 34%-54%) with information, whereas this percentage was lowest in Croatia (11%, 95% CI = 3%-19%) and Poland (15%, 95% CI = 11%-18%). Parents of children with Down syndrome had significantly lower satisfaction ratings than parents of children with CHD; 13% (95% CI = 8%-18%) reported being 'very satisfied' compared to 28% (95% CI = 23%-33%) in the CHD group. Conclusions Findings suggest that informal sources of information (e.g. support groups) are of value to parents, however, they are not deemed as trustworthy as specialist medical sources. Satisfaction ratings differed across countries and by anomaly, and were particularly low in Croatia and Poland, as well as for parents of children with Down syndrome, which warrants further investigation.